Nucleoside antibiotics: biosynthesis, regulation, and biotechnology - Niu, Guoqing; Tan, Huarong (Trends in microbiology (Regular ed.), 2015)
•Nucleoside antibiotics are broad-spectrum antibiotics with unique structural features.•Unusual enzymatic reactions occur in the biosynthesis of nucleoside antibiotics.•Biosynthesis of nucleoside antibiotics is regulated at multiple levels.•Biosynthetic studies may assist with rational design of novel antibacterial agents. The alarming rise in antibiotic-resistant pathogens has coincided with a decline in the supply of new antibiotics. It is therefore of great importance to find and create new antibiotics. Nucleoside antibiotics are a large family of natural products with diverse biological functions. Their biosynthesis is a complex process through multistep enzymatic reactions and is subject to hierarchical regulation. Genetic and biochemical studies of the biosynthetic machinery have provided the basis for pathway engineering and combinatorial biosynthesis to create new or hybrid nucleoside antibiotics. Dissection of regulatory mechanisms is leading to strategies to increase the titer of bioactive nucleoside antibiotics.